Good brother, bad brother : the story of Edwin Booth and John Wilkes Booth - Giblin, James Leonard (New York : Clarion Books, 2005)
Biography of two brothers, one revered and the other abhorred.
Includes bibliographical references (p. 223-233) and index.
BC 06/05, HB 05/05, BL 05/01/05, SJ 05/05, KK 05/01/05
1014
Keywords: Booth, John Wilkes, -- 1838-1865 -- Juvenile literature; Booth, John Wilkes, -- 1838-1865 -- Family -- Juvenile literature; Booth, Edwin, -- 1833-1893 -- Juvenile literature; Lincoln, Abraham, -- 1809-1865 -- Assassination -- Juvenile literature; Booth, John Wilkes, -- 1838-1865.; Booth, Edwin, -- 1833-1893; Lincoln, Abraham, -- 1809-1865 -- Assassination; Actors -- United States -- Biography -- Juvenile literature; Brothers -- United States -- Biography -- Juvenile literature; Actors and actresses; Brothers